Strengthening of Timber Beam with Cold-Formed Steel Plates - Yoresta, Fengky Satria; Nugroho, Naresworo (International Journal of Sustainable Construction Engineering and Technology, 2023)
This paper describes an experimental program which examined the flexural strengthening of timber beams (50x50x1000 mm) using cold-formed steel (CFS) plates (0.75 mm thick and 30 mm wide). A total of fifteen specimens were tested in three-point bending scheme with a span-depth ratio of 18:1. The effectiveness of the steel plates was evaluated for different strengthening lengths and number of strengthening layers. Test results showed that maximum load carrying capacity and stiffness of the strengthened beams can be improved by up to around 70% and 40%, respectively, relative to that of control unstrengthened beams. The increase in the percentage gain occurred as increasing strengthening length as well as number of the strengthening layers. Control unstrengthened beams demonstrated linear elastic behavior during the test whereas the strengthened beams tended to undergo a pseudo-ductile behavior. Along with it tensile failure in timber was still observed in the strengthened beams.